Down on Mainstream - Lambrecht, Luk; Leemans, Koen (Strombeek - Mechelen : bkSM beeldende kunst Strombeek/Mechelen, 2012)
Bijl, Marc ; Neirings, David ; Becha, Mo ; Schepens, Steve ; Wauman, Andy ; Zevs ; Philips, Karl ; Chisa, Anetta, Mona ; Tkacova, Lucia ; Fengler, Peter ; Fontaine, Claire
Brochure tentoonstelling + extra insert bkSM#13, Maniac Summer 2, Chantal Akerman
Down on Mainstream, De Garage, Mechelen, 28.09 - 25.11.2012 + Cultuurcentrum Strombeek, Grimbergen , 09.11 - 13.12.2012
boek